IDENTIFIKASI BLACKSPOT PADA RUAS JALAN NASIONAL DI JEMBER - Gagas Hikmah Pradana; Willy Kriswardhana; Nunung Nuring Hayati; Sonya Sulistyono (Program Studi Teknik Sipil, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2020)
Letjen Panjaitan Road and Letjen S. Parman Road are national roads connecting Jember City and Banyuwangi City. Public roads with massive traffic volumes and high accident rates are a scourge in the community. Traffic accidents result in much loss, both property and vehicle damage costs, as well as medical care costs. In order to obtain road conditions that minimize the risk of traffic accidents, it is necessary to identify locations that are prone to traffic accidents. The method for handling accident-prone locations uses the Road Infrastructure Safety Audit form. Traffic accident data from 2014-2018 obtained from the Jember Police Traffic Unit with accident-prone locations occurred in the KM 1 + 250 to KM 1 + 500 road segments. Road infrastructure safety audits get a non-hazardous (NH) risk category. The road geometry in the field is following the geometric procedures for inter-city road planning issued by the Department of Public Works and Bina Marga.